A dual‐band filtering structure for highly selective reconfigurable bandpass filter and filtering balun. Issue 8 (2nd May 2022) - Ge, Jinqun; Wang, Guoan
Abstract: This article proposes a filtering structure consisting of two half‐wavelength resonators and two open‐stub loaded resonators, which generates two third‐order passbands. Multiple transmission zeros are introduced by the newly developed coupling scheme, resulting in extremely sharp roll‐off desirable for highly selective filters. The proposed structure is applied to design a PIN‐diodes switch‐controlled reconfigurable dual‐band bandpass filter (BPF) with four‐state filtering responses: both passbands ON, both passbands OFF, high‐frequency passband ON, and low‐frequency passband ON. Stepped‐impedance open stubs and one‐end‐grounded coupled lines are studied and employed in the design to suppress unwanted responses. In addition, two filtering structures are placed symmetrically to design a dual‐band balun BPF. Double‐sided parallel‐strip lines are added in the input port of the filter, and their inherent out‐of‐phase feature enables the balun filter to convert unbalanced signal to balanced signal at desired frequencies. The measured results of both fabricated devices agree well with the simulated results. The switchable BPF and balun BPF have two passbands (2.8 and 4.8 GHz) with high selectivity with the minimum roll‐offs from −3 to −15 dB are 1.70 × 10 3 and 2.71 × 10 3  dB/decade, respectively. The insertion loss of the switchable BPF is 2.3/2.0 dB and the minimum signal suppressions level OFF state is measured as −18.2 dB. The insertion loss of the balun BPF is 1.8/1.4 dB, and the phase and magnitude imbalances are less than 0.3 dB and 5°, respectively. The excellent performances of the implemented filter and filtering balun successfully demonstrate the advantages and design efficacy of the proposed filtering structure for different applications.